Continuity of care among diabetic patients in Accra, Ghana - Awumee, Veronica; Dery, Samuel Kennedy Kangtabe (Frontiers in Public Health, 2023)
Introduction Diabetes Mellitus is a fast-rising non-contagious disease of global importance which remains a leading cause of indisposition and death. Evidence shows that effective management of Diabetes has close link with continuity of care which is known to be the integral pilar of quality care. This study therefore sought to determine the extent of continuity of care between diabetic patients and their care providers as well as factors associated with relational continuity of care. Methodology This cross-sectional, facility-based study was conducted among diabetics in Accra, Ghana. We sampled 401 diabetes patients from three diabetic clinics from the region using stratified and systematic random sampling technique. Data was collected using a structured questionnaire containing information on socio-demographic characteristics, the four dimensions of continuity of care and patients’ satisfaction. A 5-point Likert scale was used to measure patient’s perception of relational, flexible and team continuity while most frequent provider continuity was used to measure longitudinal continuity of care. Scores were added for each person and divided by the highest possible score for each domain to estimate the continuity of care index. Data was collected and exported to Stata 15 for analysis. Results The results show that team continuity was the highest (0.9) and was closely followed by relational and flexibility continuity of care (0.8) while longitudinal continuity of care was the least (0.5). Majority of patients experienced high team (97.3%), relational (68.1%) and flexible (65.3%) continuity of care. Most patients (98.3%) were satisfied with diabetes care they received from health care providers. Females had higher odds of experiencing relational continuity of care as compared to men. Also, participants with higher educational level were 5 times more likely to experience relational continuity of care than those with lower educational background. Conclusion The study demonstrated that majority of diabetics had team continuity of care being the highest experienced among the four domains, followed by flexible and longitudinal being the least experienced. Notably team and flexible continuity of care had positive association with relational continuity of care. Higher educational level and being female were associated with relational continuity of care.